Predictors of practicing universal precaution in prevention of nosocomial infection among medical and nursing students in a Nigerian teaching hospital - Balami, Lawan Gana; Ismail, Suriani; Muhamad Saliluddin, Suhainizam; Garba, Sani Hyedima (The International Journal of Health Sciences and Research, 2016)
Background: Hospital acquired infections are increasingly becoming a public health problem and happen usually as a result of poor compliance to standard precaution practices among Health Care Workers (HCW). Health care students are exposed to infectious diseases during their clinical training and may have to perform certain procedures which place this young inexperienced population at a significant risk of contracting and transmitting such diseases. Objectives: To determine the predictors of compliance with universal precaution practices among medical and nursing students in a Nigerian teaching hospital. Study design: A cross-sectional study was conducted involving 423 under-graduate medical and nursing students from University of Maiduguri Teaching Hospital. Materials and Methods: Respondents were selected using multi-stage stratified random sampling. Data was collected using a pretested structured self-administered questionnaire and analyzed using IBM-SPSS version 22. Chi-square test was used for association between categorical variables while Spearman’s correlation was used to analyze correlation between continuous variables. Logistic regression was used to determine predictors of practice. Results: The mean practice score was 63.7 ±8.7; about 72.8% had good practice. Predictors of practice were age (AOR = 1.2, 95% CI = 1.12 - 1.28) and year of studies (AOR = 2.4, 95% CI = 1.17- 5.40). Conclusion: Majority of participants had good practice scores however there is still room for improvement.